1967
DOI: 10.1111/j.1432-1033.1967.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Ion Equilibria and the Chemical Modification of Lysine and Tyrosine Residues in Bovine Carbonic Anhydrase B

Abstract: 1. Potentiometric titrations of bovine carbonic anhydrase B have been performed. On titration with acid from the isoionic point, pH 5.65, seven histidines, which are masked in the native enzyme, become protonated during a conformational change occurring in a narrow pH-range near pH 4. Concomitantly, the enzyme activity is lost. On back-titration of the acid-denatured enzyme from pH 2, all 11 histidines are titratable. The denatured enzyme shows an increase of titratable groups in the alkaline pH-range as well.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1967
1967
2008
2008

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…The change in absorptivity at 295 nm associated with ionization of one tyrosine residue was calculated from the relation: 2540 M "! xcm -t [17], where M is the molecular mass of the enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…The change in absorptivity at 295 nm associated with ionization of one tyrosine residue was calculated from the relation: 2540 M "! xcm -t [17], where M is the molecular mass of the enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…Nilsson and Lindskog demonstrated that, near pH 4, the expansion of BCA II occurs simultaneously with the protonation of seven buried His residues. 753 Because the Zn II cofactor is coordinated by three His residues, it is not surprising there is no measurable enzymatic activity at pH 3.7.…”
Section: First Transitionmentioning
confidence: 99%
“…Bovine erythrocyte carbonic anhydrase B was prepared according to the method of Lindskog [13] except that the final zone electrophoresis step was replaced by rechromatography on DEAE-cellulose [14]. Procedures spectrophotometrically at 280 mp taking the molecular extinction coefficient e2*/, = 57,000 M-l x cm-l and a molecular weight of 30,000 [17].…”
Section: Enzymementioning
confidence: 99%